Russian Students' Use of Social Network Sites for Selecting University Abroad: Case Study at the Russian State University for Humanities - Rekhter, Natalia; Hossler, Donald (Journal of International Students, 2020)
This qualitative case study explores how undergraduate students from the Russian State University for Humanities used social network sites (SNSs) for their decision to transfer to higher education institutions (HEIs) abroad. Participants reported using specific SNS features, such as likes and shares, for measuring HEI rating and indicated that ability to use native language was among motivating factors for membership in a specific SNS. The reported benefits of SNSs included instantaneous connections with likeminded individuals, realistic visualization of campuses, and unbiased and multidimensional views presented by SNS members. One of the emerging findings was that participants with no connections abroad relied exclusively on SNSs for their college choice. Participants with connections abroad relied on the advice of international contacts, and SNSs played a complementary role. HEI professionals may consider hiring and training international students to maintain consistent and meaningful content on different SNS platforms, particularly in their countries’ specific SNSs.